Ethnobotany of Traditional Food Ingredients in Tuban Regency, East Java - Kurniahu, Hesti; Andriani, Riska; Rahmawati, Annisa (Universitas Labuhanbatu, 2023)
Traditional food is one of the cultural products that was created to meet primary human needs by involving local wisdom. Various types of traditional food are processed from plants taken from the surrounding environment and other places. Local communities have specific interactions and perceptions of plants as ingredients for their traditional foods. The goal was to determine the diversity, the categories of utilization, the organs used, the preparation methods, and the Cultural Significance Index (ICS) of plants in traditional Tuban food ingredients. This research was conducted by surveying 117 respondents from 20 sub-districts in Tuban Regency, followed by in-depth interviews with 20 traditional food makers in Tuban. The data obtained is in the form of qualitative data in the form of local knowledge of the Tuban people regarding plants in their traditional food ingredients, while quantitative data is in the form of the Cultural Significance Index (ICS). The results showed that there were 15 families consisting of 10 species of plants in traditional Tuban food, all of which were cultivated plants, the most used category of plants as spices and the organs most used were seeds and the highest ICS value was Oryza sativa L.Â